Analisis Faktor Integrasi Sosio-Kultural-Historis pada Masyarakat Multikultural - Muhamad Arif (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2016)
AbstractPost-1998 reform of the Indonesian nation was shocked by the social conflict that was previously unimaginable. The social conflict immediately arouse awareness to build a positive attitude through the effort to explore the factors of integration in a society. This article aims to explore the factors of integration in a multicultural society. For qualitative descriptive study was carried out, by doing participant observation, in-depth interviews, and documentation. The result was found three factors of integration as follows. First, the historical factors concerning the friendly relations between the Mataram kingdom and the kingdom of Buleleng, which boiled down to the relationship of brotherhood and kinship, between the Muslims and the Hindus that took place since the 17th century. Secondly, the occurrence of inter-ethnic marriages (amalgamation) among the Javanese and Balinese thus eliminating the psychological distance and distance sociological, reinforced with Menyama Braya conception and Ukhuwah Basyariah conception. Third, assimilation and acculturation between Islamic culture and the culture of Bali that still survive today.AbstrakPasca reformasi 1998 bangsa Indonesia dikejutkan oleh konflik sosial yang tak terbayangkan sebelumnya. Konflik sosial tersebut segera menggugah kesadaran untuk membangun sikap positif melalui upaya menggali factor-faktor integrasi dalam suatu masyarakat. Artikel ini bertujuan untuk menggali faktor-faktor integrasi dalam masyarakat Pegayaman yang multikultural. Untuk itu dilakukan penelitian deskriptif kualitatif, dengan melakukan observasi partisipatif, wawancara mendalam, dan studi dokumentasi. Hasilnya adalah ditemukan adanya tiga faktor integrasi sebagai berikut. Pertama, faktor historis menyangkut hubungan persahabatan antara kerajaan Mataram dan kerajaan Buleleng, yang mengerucut pada hubungan persaudaraan dan kekeluargaan, antara orang-orang Islam dan orang-orang Hindu yang berlangsung sejak abad ke-17. Kedua, terjadinya perkawinan antaretnik (amalgamasi) antara orang-orang Jawa dengan orang-orang Bali sehingga menghilangkan jarak psikologis dan jarak sosiologis, yang diperkuat dengan konsepsi menyama braya dan konsepsi ukhuwah basyariah. Ketiga, terjadinya asimilasi dan akulturasi antara budaya Islam dan budaya Bali yang masih bertahan hingga saat ini.Pengutipan: Arif, M. (2016). Analisis Faktor Integrasi Sosio-Kultural-Historis pada Masyarakat Multikultural. SOSIO DIDAKTIKA: Social Science Education Journal, 3(2), 2016, 126-134. doi:10.15408/sd.v3i2.4374.Permalink/DOI: http://dx.doi.org/10.15408/sd.v3i2.4372